Analisis Pengaruh Kepuasan Kerja Terhadap LoyalitasKaryawan Dengan Pengelolaan Strees Kerja Sebagai Variabel moderating (Studi Pada PT. Tirta Investama Klaten) - Irawan, Bayu Hendra, Drs. Farid Wajdi, MM, Ph.D (2016)
Job satisfaction is one of the factors that should be owned by the employees to obtain optimal results. The work of satisfaction would arise the feeling loyal to the company where he worked. Loyalty work owned by the employees will encourage them to contribute actively to promote the company. In order for all this to be realized it is necessary to work a good stress management within the company. That is because the employee within the company must have a good level of work stress was low or high. This research was conducted at PT. Tirta Investama Klaten. This study aims to determine the effect of job satisfaction on employee loyalty by job stress management as moderating variable. The number of samples set out in this study were 60 respondents using purposive sampling method. As independent variables, job satisfaction and the dependent variable is employee loyalty and moderating variable is the management of occupational stress. The analysis includes the validity, reliability, classic assumption test, simple linear regression analysis and moderating. Results of analysis using simple linear regression (for hypothesis 1) and moderating (hypothesis 2) so that it can be seen that the variable job satisfaction has positive effect directly significant to the loyalty of employees (H1), and variable interactions between the relationship of job satisfaction with the management of work stress effect negatively on employee loyalty (H2). The results of the analysis using the t test knowable job satisfaction and interaction between job satisfaction and job stress management significantly influence employee loyalty.